A Preliminary Note on the Occurrence of a Species of Helopeltis, (Capsidae, Rhynchota) on Nursery Seedlings - Viswanathan, T. P. (Indian Forester, 1949)
Both adults and nymphs of a species of Helopeltis very near anlonii (Capisdae), have been recordcd doing serious damage to the nursery seedlings of Terminalia tomtentosa and Lagerstroemia fos-reginae at Parumpavoor. The food plants of H. antonli sign., are Anacardium occidentale, Bixa orellana, Cocao, Cinchona, Cinnamonum camphora, Erythrina AleNa azadirachta, Swietenia, tea, Tephrosia, and Cucurbitaceae. Their feeding causes distortions on the leaves and shoots. Fish oil soap solution has been found effective in controlling the ling.